Extracellular vesicles released by mesenchymal-like prostate carcinoma cells modulate EMT state of recipient epithelial-like carcinoma cells through regulation of AR signaling. (1st December 2017) - El-Sayed, Ihsan Y.; Daher, Ahmad; Destouches, Damien; Firlej, Virginie; Kostallari, Enis; Maillé, Pascale; Huet, Eric; Haidar-Ahmad, Nathaline; Jenster, Guido; de la Taille, Alexandre; Abou Merhi, Raghida; Terry, Stéphane; et al.
Abstract: Extracellular vesicles released from cancer cells may play an important role in cancer progression by shuttling oncogenic information into recipient cells. However, our knowledge is still fragmentary and there remain numerous questions regarding the mechanisms at play and the functional consequences of these interactions. We have recently established a mesenchymal-like prostate cancer cell line (22Rv1/CR-1; Mes-PCa). In this study, we assessed the effects of the extracellular vesicles released by these cells on recipient androgen-dependent epithelial VCaP prostate cancer cells. Mes-PCa derived vesicles were found to promote mesenchymal features in the recipient epithelial-like prostate cancer cells. This transformation was accompanied by a modulation of androgen receptor signaling and activation of TGFβ signaling pathway. Moreover, recipient cells acquiring mesenchymal traits displayed enhanced migratory and invasive features as well as increased resistance to the androgen receptor antagonist, enzalutamide. Our results suggest a previously unappreciated role for Mes-PCa secreted vesicles in cancer promotion by transferring cell-mediated signals and promoting phenotypic changes in recipient prostate cancer cells. Highlights: We reveal an unknown role of EVs shed by Mes-PCa cells in modulating AR signaling and mediating EMT in recipient PCa cells. Recent research focuses on the capacity of cancer cells to shed EVs of various sizes and functions into the microenvironment. Cancer-derived vesicles' potential in shaping pro-metastatic niches and enhancing metastasis is evoked in many cancer types. We highlight a new function of Mes-PCa-EVs on AR-dependent PCa cells in terms of reducing AR and activating TGFβ pathway. We show that Mes-PCa-EVs can contribute to PCa heterogeneity by promoting intermediate EMT cell states. This study provides evidence that Mes-PCa-EVs can stimulate tumor aggressiveness and anti-AR therapy resistance.